An all-out sprint does not challenge the main goal of an endurance-based training session in cycling - Demay, R. S.; Kerhervé, H. A. (European Journal of Applied Physiology, 2025)
Purpose This study investigated the acute and delayed effects of a prolonged, moderate-intensity training session with or without an interspersed all-out exercise on exercise capacity, physiological responses, and perceptual responses. Methods Eighteen trained cyclists and triathletes (24.4±2.6 years; 70.4±8.5 kg; 66.5 ± 9.5 ml min kg-1 VO2max) performed two 3-h cycling sessions, either continuously (CON) or interspersed (INT) with an all-out effort. Metabolic energy expendi ture (Met-EE), respiratory exchange ratio (RER), blood lactate (BLa) and ratings of perceived exertion (RPE) were assessed every 30 min. In each session, a 3-min all-out test (3MAOT) was performed before (PRE), immediately after (POST), and 48 h after (REC) the prolonged effort to estimate alterations and recovery in exercise capacity. In INT, an additional 3MAOT was performed at 90 min (MID). Results Overall mechanical energy expenditure (Mec-EE) was significantly higher in INT (p<0.001). Met-EE measured at 30-min intervals did not change over time (p=0.166), and RER decreased significantly in both trials (p<0.001), with no differences between CON and INT. RPE increased significantly over time (p<0.001), with no differences between conditions (p=0.272). At POST, while end-test power (EP) remained unchanged, total work done (TWD) and work above EP (WEP) significantly decreased (p<0.001) with no differences between conditions. At REC, TWD and WEP were significantly higher than at POST (p<0.01) and not different from PRE (p=1.0), with no differences between conditions. Conclusion A 3MAOT performed during an endurance-based training session did not alter metabolism or perceived exer tion, nor did it affect delayed exercise capacity beyond the effect of the 3-h prolonged exercise itself. There appears to be no physiological basis for the strict exclusion of short, high-intensity bursts during endurance training.